Enhancing the field of view of cat-eye retroreflectors by simply matching the mirror radius of curvature and the lens focal length - Quan Sheng; Aihua Wang; Yue Qi; Meng Wang; Zheng Shi; Jingni Geng; Junjie Liu; Sijia Wang; Shijie Fu; Wei Shi; Jianquan Yao (Results in Physics, 2022)
The field curvature (FC) induced defocusing is the main issue which limits the effective field of view (FoV) of cat-eye retroreflectors (CERs). We found that for a certain common spherical lens, there exists an optimal mirror radius of curvature (ROC), which is different from the focal length f of the lens and could minimize the FC-induced defocusing. Therefore, the effective FoV of the CERs can be enhanced by simply optimizing the relationship between the lens focal length and the mirror ROC. The optimizing criterion and calculation results are discussed here. Improved CERs with off-the-shelf components were used as the output coupler of a Nd:GdVO4 laser cavity for its alignment-free operation. Compared with the conventional CERs with mirror ROC equals to the lens focal length and with flat mirror, the improved CERs exhibited significantly improved FoVs.